Implementasi Program Pengembangan dan Perlindungan UMKM Pada Dinas Perdagangan, Koperasi, dan Usaha Mikro Kabupaten Bojonegoro - Tauran; Moch. Faisal Elfadila; Suci Megawati; Ahmad Nizar Hilmi (Publika, 2025)
MSMEs are economic activities that play a strategic role in reducing economic disparities and increasing national economic growth. Therefore, the development and protection of MSMEs are an important agenda in development policies. In response to this development, the Bojonegoro Regency Government issued Regional Regulation No 2 of 2020 concerning the Development and Protection of Cooperatives and Micro Enterprises. This regulation has been in effect for five years, but the implementation of the program still faces obstacles, such as limited public knowledge regarding the development and protection of MSMEs, low participation of MSME actors, and obstacles to socialization and coordination between agencies. This study aims to analyze the implementation of the MSME development and protection program at the Bojonegoro Regency Trade, Cooperatives, and Micro Enterprises Office (Disdagkop UM) using qualitative descriptive research methods. The analytical framework of this study uses the Van Meter and Van Horn policy implementation model, which focuses on six main variables: policy standards and objectives, resources, characteristics of implementing organizations, inter-organizational communication, implementer disposition, and social, economic, and political conditions that have a direct impact on the success of the policy. The research data collection consisted of interviews with the Bojonegoro Regency Trade, Cooperatives, and UM Office, direct observation at the relevant locations, and analysis of official documents related to MSME development and protection policies. The research results show that this program has succeeded in growing the economic activity of MSME actors, however, obstacles still arise such as obstacles in reaching all levels of society and minimal involvement of MSME actors. Recommendations that can be given include increasing socialization and coordination between agencies with other agencies with the aim of the program's success in the future.